Childhood Stroke and Congenital Heart Disease - Laurence Ducharme-Crevier; Mark S Wainwright (Pediatric Neurology Briefs Publishers, 2015)
Investigators from the University of California performed a case-control study of the association of stroke with congenital heart disease (CHD) within a population of 2.5 million children in Northern California.